2018
DOI: 10.1200/jgo.18.18500
|View full text |Cite
|
Sign up to set email alerts
|

Future Burden of Cancer Attributable to Current Modifiable Behaviours: A Pooled Study of Seven Australian Cohorts

Abstract: Background: The Population Attributable Fraction (PAF) quantifies the fraction of cancer cases attributable to specific exposures. PAF estimates for the future burden of cancer preventable through modifications to current exposure distributions are lacking. Previous PAF studies have also not compared population subgroup differences. Aim: To apply a novel PAF method and i) assess the future burden of cancer in Australia preventable through modifications to current behaviors, and ii) compare the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although lifestyle factors such as tobacco smoking and alcohol use are responsible for a large proportion of cancers [ 14 ], research on common modifiable risk factors for MM has been limited by the inability of smaller observational studies to detect effects of public health significance [ 4 ]. Large observational studies and meta‐analyses have indicated that while tobacco smoking is unlikely to be associated with MM risk [ 15 17 ], alcohol consumption may be inversely associated [ 15 , 18 22 ], and this inverse association is possibly stronger for women, and wine drinkers [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although lifestyle factors such as tobacco smoking and alcohol use are responsible for a large proportion of cancers [ 14 ], research on common modifiable risk factors for MM has been limited by the inability of smaller observational studies to detect effects of public health significance [ 4 ]. Large observational studies and meta‐analyses have indicated that while tobacco smoking is unlikely to be associated with MM risk [ 15 17 ], alcohol consumption may be inversely associated [ 15 , 18 22 ], and this inverse association is possibly stronger for women, and wine drinkers [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%